2001
DOI: 10.1117/1.1381561
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulse duration on ultrashort laser pulse ablation of biological tissues

Abstract: Ablation characteristics of ultrashort laser pulses were investigated for pulse durations in the range of 130 fs-10 ps. Tissue samples used in the study were dental hard tissue (dentin) and water. We observed differences in ablation crater morphology for craters generated with pulse durations in the 130 fs-1 ps and the 5 ps-10 ps range. For the water experiment, the surface ablation and subsequent propagation of stress waves were monitored using Mach-Zehnder interferometry. For 130 fs-1 ps, energy is deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 23 publications
1
35
0
6
Order By: Relevance
“…The final signal shown in figure 5B is the superposition of these two waves. Interestingly, oscilloscope traces with spikes very similar to those obtained here are shown in recent studies where a PDVF sensor was developed to monitor nanosecond laser induced-bubble collapse near a solid surface 11,12 . Clearly the laser exposure configuration used in the present study is very different from that bubble collapse is not the mechanism responsible to produce such spikes in our experiments.…”
Section: Pressure For Different Irradiation Configurationssupporting
confidence: 72%
“…The final signal shown in figure 5B is the superposition of these two waves. Interestingly, oscilloscope traces with spikes very similar to those obtained here are shown in recent studies where a PDVF sensor was developed to monitor nanosecond laser induced-bubble collapse near a solid surface 11,12 . Clearly the laser exposure configuration used in the present study is very different from that bubble collapse is not the mechanism responsible to produce such spikes in our experiments.…”
Section: Pressure For Different Irradiation Configurationssupporting
confidence: 72%
“…Evidence of melting and thermal damage was observed at the walls and edges of the 5 ps and 10 ps craters. A separate experiment, using water, confirmed the transition of ablation characteristics in the range of 1 ps -5 ps [11]. It was found that a significant amount of energy of 5 ps or longer pulses penetrates through the plasma layer and is volumetrically absorbed along the beam axis.…”
Section: Yearmentioning
confidence: 56%
“…A computer-controlled feedback system utilized the high intensity luminescence of calcium at 616 nm and it was used in selective ablation of the bone tissues successfully [10]. Ablation thresholds were measured for hard dental tissues (dentin) and water and it was found that the threshold increases at longer pulse widths [6,11]. It was found that the threshold increased as the square root of pulse width for pulses longer than several picoseconds.…”
Section: Yearmentioning
confidence: 99%
“…5 Consequently, laser machining with little heat deposition is possible when the wavelength of an ultrafast laser is tuned away from the material absorption. Recently, several papers [6][7][8][9] have reported promising hard-tissue machining by using infrared laser pulses with mJ or sub-mJ pulse energy and ps to fs pulse width at kHz repetition rates. However, the laser system used for those studies requires a fairly complex and expensive laser amplifier seeded by a mode-locked laser oscillator.…”
mentioning
confidence: 99%
“…In most previous studies, [6][7][8][9] visible surface damage on a scanning electron microscopic image was considered an important signature of the ablation threshold or was used to determine the material cutting rate. However, on many occasions, the cutting or drilling process can be abruptly stopped due to carbonization or plasma plume on the tissue surface.…”
mentioning
confidence: 99%